The Effect of Sanyinjiao Point Accupressure Therapy (SP6) on Reducing Primary Dysmenorrhea Pain Intensity - Sin Wajo; Nur Rahmawati Sholihah (Universitas Jenderal Achmad Yani Yogyakarta, 2023)
Background: Dysmenorrhea is a gynecological problem that often occurs in women during menstruation. In Indonesia, the incidence of dysmenorrhea is 64.25%, while 52% of students in Yogyakarta experience a decrease in the productivity of daily activities during menstruationObjective: To determine the effect of sanyinjiao point acupressure therapy (SP6) on reducing the intensity of primary dysmenorrhea pain Methods: Pre-Experimental research method, one group pretest-posttest design. Purposive sampling technique. The intervention group was given Sanyinjiao point acupressure (SP6). Dysmenorrhea pain variables were measured using NRS. Univariate analysis uses frequency distribution and bivariate analysis uses Wilxocon.Results: The results of statistical tests showed that there was a significant difference between before and after the intervention with a p-value of 0.000. Before the intervention was given an average of 5.29 dysmenorrhea pain, after the intervention experienced a decrease in dysmenorrhea pain intensity by an average of 1.75. Conclusion: There is an effect of sanyinjiao point acupressure therapy (SP6) on reducing the intensity of primary dysmenorrhea pain with a p-value of 0.000 and a decrease in dysmenorrhea pain of 3.54.